2020
DOI: 10.1098/rspb.2020.1134
|View full text |Cite
|
Sign up to set email alerts
|

Riddles in the cold: Antarctic endemism and microbial succession impact methane cycling in the Southern Ocean

Abstract: Antarctica is estimated to contain as much as a quarter of earth's marine methane, however we have not discovered an active Antarctic methane seep limiting our understanding of the methane cycle. In 2011, an expansive (70 m × 1 m) microbial mat formed at 10 m water depth in the Ross Sea, Antarctica which we identify here to be a high latitude hydrogen sulfide and methane seep. Through 16S rRNA gene analysis on samples collected 1 year and 5 years after the methane seep formed, we identify the taxa involved in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 51 publications
0
24
0
1
Order By: Relevance
“…Despite being persistently cold and having little to no sunlight in the winter, considerable areas of the Southern Ocean (SO) are biologically productive regions that play central roles in nutrient recirculation, supporting primary production across global ocean scales and mediating CO 2 exchange and sequestration via the biological pump (Álvarez et al ., 2002; Arrigo et al ., 2008; Lenton et al ., 2013; Legge et al ., 2015). The SO is also an important region for recirculation of climate active trace gasses such as dimethyl sulfoxide and methane (Curran and Jones, 2000; Gabric et al ., 2001; Wadham et al ., 2012; Thurber et al ., 2020). Prokaryotes (domain Bacteria and Archaea ) make up the largest proportion of microbial biomass in open SO waters and are primary drivers of biogeochemical cycling (Wilkins et al ., 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Despite being persistently cold and having little to no sunlight in the winter, considerable areas of the Southern Ocean (SO) are biologically productive regions that play central roles in nutrient recirculation, supporting primary production across global ocean scales and mediating CO 2 exchange and sequestration via the biological pump (Álvarez et al ., 2002; Arrigo et al ., 2008; Lenton et al ., 2013; Legge et al ., 2015). The SO is also an important region for recirculation of climate active trace gasses such as dimethyl sulfoxide and methane (Curran and Jones, 2000; Gabric et al ., 2001; Wadham et al ., 2012; Thurber et al ., 2020). Prokaryotes (domain Bacteria and Archaea ) make up the largest proportion of microbial biomass in open SO waters and are primary drivers of biogeochemical cycling (Wilkins et al ., 2013b).…”
Section: Introductionmentioning
confidence: 99%
“…Below the former Larsen B ice shelf, a low-activity seep (Niemann et al, 2009) with a seep-specific nematode fauna (Hauquier et al, 2011) was observed and analysed, while a small patch of bacteria occurred on the sediment at a different location (Gutt et al, 2011). In the Ross Sea at 10 m water depth a bacterial mat, based on a hydrogen sulfide and methane seep was discovered, and may have an impact on greenhouse gas emission from marine methane reservoirs (Thurber, Seabrook & Welsh, 2020). On land, geothermally active regions allow species to survive in isolation on ice-free land or in sub-ice caves, from which recolonisation of the rest of the continent could have taken place (Fraser et al, 2014).…”
Section: (D) Sentinel Species and Communities Warn Of Environmental Changesmentioning
confidence: 99%
“…The Arctic sea ice and methane triggers and positive feedbacks were explained. There are signs the methane feedback has started, as recently methane has been found to be bubbling from the floor of the Ross Sea in the Antarctic (Thurber et al, 2020). The boreal forest situation is different.…”
Section: Earth's Shifting Spheresmentioning
confidence: 99%